2017
DOI: 10.3390/foods6080069
|View full text |Cite
|
Sign up to set email alerts
|

Application of Surfactant Micelle-Entrapped Eugenol for Prevention of Growth of the Shiga Toxin-Producing Escherichia coli in Ground Beef

Abstract: Beef safety may be compromised by O157 and non-O157 Shiga toxin-producing Escherichia coli (STEC) contamination. The capacity of surfactant micelles loaded with the plant-derived antimicrobial eugenol to reduce STEC on beef trimmings that were later ground and refrigerated for five days at 5 ± 1 °C was tested to determine their utility for beef safety protection. STEC-inoculated trimmings were treated with free eugenol, micelle-encapsulated eugenol, 2% lactic acid (55 °C), sterile distilled water (25 °C), or l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Relatively high CMC values for traditional surfactants result in decomposition of micelles on individual molecules due to dilution, so their application for drug delivery is very restricted. In general, conventional surfactants are used to stabilize nano- and microemulsions for drug delivery [ 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Relatively high CMC values for traditional surfactants result in decomposition of micelles on individual molecules due to dilution, so their application for drug delivery is very restricted. In general, conventional surfactants are used to stabilize nano- and microemulsions for drug delivery [ 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The prevention of growth of Escherichia coli in ground beef by the application of surfactant micelle-entrapped eugenol was the objective proposed in the paper by Tolen et al [ 13 ]. In this case the authors concluded that this antimicrobial treatment did not significantly decontaminate ground beef and so further studies must be proposed to increase the utility of these EOs for beef safety protection.…”
Section: Introductionmentioning
confidence: 99%
“…Further results showed that after five days of storage, all treatments significantly reduced the pathogenic load by 0.2 and 0.3 log 10 CFU/g (p=0.014) [17]. Tolen et al [18] evaluated the synergistic blend of sodium dodecyl sulfate (SDS), lactic acid (LA) and chitosan acid (CA) against non-STEC O157 using cattle hide decontamination model. The treatments were (vol/vol): CA (1% chitosan in 1% acetic acid), SDS (1%), SDS (2%), LA (1%), CA-SDS combination (1% chitosan in 1% acetic acid mixed with 1% SDS), and LA-SDS combination in two different concentrations (1% LA mixed with 1% SDS, and 1% LA mixed with 2% SDS) and phosphate buffer water as a control.…”
Section: Introductionmentioning
confidence: 99%